2002
DOI: 10.1038/sj.gt.3301647
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhotic rat livers with extensive fibrosis can be safely transduced with clinical-grade adenoviral vectors. Evidence of cirrhosis reversion

Abstract: Adenoviral vectors efficiently target normal liver cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 27 publications
4
63
0
3
Order By: Relevance
“…Recent reports describe that transduction efficiency by adenoviral-mediated gene transfer reduced after liver injury, but remained significant. 12 As documented in previous studies, the administration of adenovirus is an effective means to direct transgene expression in liver as assessed by visual detection of transduced GFP or b-Gal (data no shown). However, compared with normal controls, transgene expression as assessed by the delivery of an Ad-GFP or Ad-b-Gal reporter was significantly reduced in BDL/Mn 2+ cirrhotic rats.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Recent reports describe that transduction efficiency by adenoviral-mediated gene transfer reduced after liver injury, but remained significant. 12 As documented in previous studies, the administration of adenovirus is an effective means to direct transgene expression in liver as assessed by visual detection of transduced GFP or b-Gal (data no shown). However, compared with normal controls, transgene expression as assessed by the delivery of an Ad-GFP or Ad-b-Gal reporter was significantly reduced in BDL/Mn 2+ cirrhotic rats.…”
Section: Discussionsupporting
confidence: 57%
“…However, compared with normal controls, transgene expression as assessed by the delivery of an Ad-GFP or Ad-b-Gal reporter was significantly reduced in BDL/Mn 2+ cirrhotic rats. 12 Several gene therapy approaches have successfully prevented and halted the progression of liver fibrosis in experimental models. However, because fibrotic liver disease may not be clinically detected until an advanced stage with concomitant appearance of disturbances in the central nervous system, that is, HE, the possibility of reversing established fibrosis becomes an essential issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When adenovirus vectors were systemically injected into rodents with normal liver, 80-90% of the vector is found in the liver and most vectors target hepatocytes. 36,37 Several reports showed that adenovirus-mediated transgene expression was preferentially shown in septal cells rather than in hepatocytes in cirrhotic rats, 15,38,39 and Nakamura et al 15 have hypothesized that the reduction of intralobular hemodynamics by the shunt formation between portal and central veins resulted in the shift of Adenovirus-mediated IFN gene therapy for LC in rat K Suzuki et al gene expression from hepatocytes to septal cells in cirrhotic rats. In this study also, the expression of lacZ and AP genes was mainly detected in the fibrous septa of cirrhotic liver after the intravenous injection of vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Other techniques include nonquantitative or semiquantitative PCR, FISH (approx. 50%), Southern blot 1,2 and reporter gene expression (LacZ, [1][2][3][4][5][6]7 luciferase, [8][9][10][11] and GFP 12 ).…”
Section: Technique Validationmentioning
confidence: 99%